1968
DOI: 10.1126/science.160.3832.1123
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin: Effects on Fish and Frog Melanophores

Abstract: Tetrodotoxin blocks the response of killifish melanophores to electrical stimulation of their melanin-aggregating nerves. The direct response of killifish or frog melanophores to hormones is not affected. Since there is no effect on melanin aggregation resulting from the release of adrenergic neurotransmitter in killifish melanophores, we conclude that tetrodotoxin acts by blocking nerve conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In another retinal mutant, noa, in which there appears to be a failure of synaptic transmission, the melanophores are chronically expanded (Brockerhoff et al, 1995). The pigmentation of melanophores is controlled both by neural input to the cells and by circulating neural hormones (Ujii and Novales, 1968;Bagnara, 1972). Melanin granules in zebrafish melanophores aggregate in the light and disperse in the dark, causing darkening of zebrafish at night and blanching during the day.…”
Section: Discussionmentioning
confidence: 99%
“…In another retinal mutant, noa, in which there appears to be a failure of synaptic transmission, the melanophores are chronically expanded (Brockerhoff et al, 1995). The pigmentation of melanophores is controlled both by neural input to the cells and by circulating neural hormones (Ujii and Novales, 1968;Bagnara, 1972). Melanin granules in zebrafish melanophores aggregate in the light and disperse in the dark, causing darkening of zebrafish at night and blanching during the day.…”
Section: Discussionmentioning
confidence: 99%
“…In the killifish Fundulus heteroclitus, Fujii and Novales (1968) showed that tetrodotoxin effectively blocked the conduction of melanin-aggregating fibers, but not the responsiveness of melanophores per se. Their results also indicated that Na + -dependent action potentials are not involved in the responsiveness of the effector cells.…”
Section: Other Chemical Factors Influencing Chromatophoresmentioning
confidence: 99%
“…Fujii (1961) also found that the effect of K + ions could be blocked by treatment with the adrenergic blocking agent dibenamine. Furthermore, Fujii and Novales (1968) showed that the response to K + ions could still be observed after treatment with tetrodotoxin, which effectively blocked the conduction of pigment-aggregating nerves. The results also indicated that active electrical events due to the entry of Na + ions are not involved in the motile activity of the cells.…”
Section: Substances That Modify Hormonal and Nervous Signalsmentioning
confidence: 99%
“…It is known that such an electrical field stimulates sympathetic fibers to liberate neurotransmitters (Fujii and Novales, 1968). The stimulating waves were monitored by a storage oscilloscope (5111A, Tektronix, Beaverton, OR).…”
Section: Nervous Stimulationmentioning
confidence: 99%